A Study of Code Switching Found in English Teaching Activities at SMAN 1 Wungu Madiun - Al Rosyiidah, Afiifah; Farida, Siti (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
Code switching refers to a phenomenon that people switch between different languages in a conversation. Code Switching also occurs in English teaching activities. This study aims to explain the types and reasons of code switching found in English teaching activities at SMAN 1 Wungu Madiun. The data of this research are utterances contain code switching used by English teacher in 10th grade of SMAN 1 Wungu Madiun. This study uses qualitative research because the data in the form of words. The result of this study shows that there are two types of code switching found in English teaching activities at SMAN 1 Wungu Madiun, they are metaphorical code-switching (4 data) and situational code switching (83 data). In addition, it shows that there are ten reasons of code switching in English teaching activities at SMAN 1 Wungu Madiun: talking about particular topic (19 data), quoting somebody else (5 data), showing empathy about something (5 data), interjection (4 data) , repetition used for clarification(7 data), intention of clarifying the speech content for the interlocutor (21 data) , expressing group identity (4 data) , to soften or strengthen request or command (10 data) , lexical need (1 data) , to exclude other people when a comment is intended for only a limited audience (3 data).